The journalism crisis: echoes and silences in the practices and narratives - Berger Ramos Kuschick, Christa Liselote (2015)
Researchers and journalists are dedicated to understand the tensions that shake the production system of journalism, which has had certain hegemony as social reference speech  (GOMIS, 1999). This article reflects on how the crisis journalism has appeared in speeches and in the press itself practices. The initial suspicion is that the crisis sets in muted event by the mainstream media. Moreover, it inevitably also transpires in newspaper practice, once it has reached the working structure of essays. It has caused journalists to review their skills and transform the field - in a way - their assumptions and ways of doing.